Qualitative factors affecting IT/IS startups valuation - Maheshwari, Vishal; Kumar, Senthil; Yew, Beh Ching; Wah, Ooi Bee; Yee, Angelina Seow Voon; Abdul Razak, Shazrul Ekhmar; Ramachandran, Jayalakshmy (Malque Publishing, 2025)
This systematic literature review explores the multifaceted qualitative factors influencing the valuation of Information Technology/Information Systems (IT/IS) startups. These startups, characterized by rapid development cycles and disruptive technologies, face unique challenges and opportunities within volatile markets. Key qualitative factors identified include Technology Readiness Levels (TRLs), Intellectual Property (IP), founder and management team characteristics, strategic partnerships, funding, geographical location, and business strategy. The review highlights the critical role these non-financial metrics play in assessing startup potential and valuation. Limitations arise from the scope of available evidence and reliance on secondary sources. The findings lead to the development of a nuanced evaluation framework that can assist startup founders in strengthening their qualitative factors, thereby achieving fair and robust valuations. This framework is crucial for guiding strategic decision-making, enhancing investor confidence, and supporting sustainable growth and competitive advantage in the evolving IT/IS landscape.